2021
DOI: 10.1155/2021/6628778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PPA on the Short‐Term Antiaging Performance of Asphalt

Abstract: It has been confirmed that polyphosphoric acid (PPA) can significantly improve the high-temperature resistance, storage stability, and aging resistance of asphalt. The low price of PPA is conducive to the development of modified asphalt with high performance and excellent economy, suggesting its great application prospects. At present, there is little research on the role of PPA in delaying the aging process of PPA-modified asphalt, and a consensus has not yet been reached. Therefore, PPA-modified asphalt with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Therefore, for a clean manufacture of rubberised bituminous mix, the manufacturing temperature should be reduced without sacrificing mechanical performance. For this reason, a wide range of additives that can increase distinct characteristics of bitumen and work in diverse ways have been utilised in rubberised bitumen modification, such as PPA, Evotherm, MPP, TMQ and sulphur, which were identified as co-modifiers [4,12,22,23,30,33,34].…”
Section: Type Of Additives and Their Methods Of Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for a clean manufacture of rubberised bituminous mix, the manufacturing temperature should be reduced without sacrificing mechanical performance. For this reason, a wide range of additives that can increase distinct characteristics of bitumen and work in diverse ways have been utilised in rubberised bitumen modification, such as PPA, Evotherm, MPP, TMQ and sulphur, which were identified as co-modifiers [4,12,22,23,30,33,34].…”
Section: Type Of Additives and Their Methods Of Applicationmentioning
confidence: 99%
“…NR has two main types: natural rubber latex (NRL) and a new type of NR known as cup lump natural rubber (CLNR) (Figure 1), which is produced when latex is allowed to coagulate under bacterial attack [12,13]. NRL polymer can be used as a modifier to enhance bitumen's physical qualities, such as increasing the softening point, reducing penetration while enhancing the penetration index, and improving the properties of shortand long-term ageing [3,14,15].…”
Section: Natural Rubber As a Bitumen Modifiermentioning
confidence: 99%
See 1 more Smart Citation
“…From the micro perspective, PPA is found to significantly improve the adhesion ability, high temperature elasticity, and rutting resistance of SBRMA through reverse flocculation; the incorporation of PPA also reduces the size of the polymer dispersed phase, which forms a more ideal microstructure and significantly enhances the compatibility of SBR and asphalt [ 19 ]. In regard to the mechanism of PPA improving the thermal oxygen aging resistance of asphalt, it has been suggested that PPA causes a gelation effect on asphalt and can disperse agglomerates of asphaltene micelles, which significantly reduces the impact of aging on the asphalt properties [ 20 , 21 ]. In addition, Han et al [ 22 ] argued that a chemical reaction between PPA and the reactive groups in SBS-modified asphalt resulted in a tighter cross-linked network structure of the SBS-modified asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…Rutting, a permanent deformation in the wheel path brought on by traffic loads, is more prevalent during hotter months [14]. When choosing pavement materials, high-performance bitumen with hightemperature stability should be taken into consideration to reduce pavement rutting and extend the service life of bitumen pavement [15].…”
Section: Introductionmentioning
confidence: 99%